Morphological Features Of The Gastric Mucosa In Critically Ill Patients On Artificial Lung Ventilation (Eurasian Research Bulletin, 2024)
It has long been known in medical practice that the gastrointestinal tract (GIT) fulfils not only digestive function. The GIT tract is also an important endocrine organ that synthesises many hormones involved in the regulation of protein, fat and carbohydrate metabolism, having a systemic effect on the body. The walls of the gastrointestinal tract contain about 100 million neurons that constantly control its activity, as well as about 60-70% of the body's lymphoid tissue, which plays a key role in immune defence. There are convincing data supporting the link between the GI tract condition and the development of systemic inflammatory response, as well as multi-organ failure, which is due to disturbances of microcirculation in the villous layer of the intestine and high sensitivity of tissues to hypoxia (Swank G.M., Deitch E.A., 1996). This study emphasises the relevance of studying the gastric mucosa in critically ill patients on artificial ventilation